Problemas actuales de la historia (UNIVERSIDAD DE SALAMANCA, 1994)
CONTENIDO : SANCHEZ NISTAL, J.M.; MONTANARI, M.; MALPICA CUELLO, A.; BARROS, C.; FERNANDEZ DE PINEDO, E.; CONTRERAS, J.; GELMAN, J.D.; FISHER, J.; DUMOULIN, M.; PEREZ LEDESMA, M.; ACEÑA, P.M.; CLAVERO, B.; FERNANDEZ BUEY, F.; MORALES MOYA, A.